2007
DOI: 10.1042/cs20060128
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines, behaviour and age as determinants of self-rated health in women

Abstract: Self-rated health is a powerful and independent predictor of long-term health, but its biological basis is unknown. We have shown previously that self-rated health is associated with increased levels of circulating cytokines in women. The main aim of the present study was to increase the understanding of the association between markers of wellbeing, such as self-rated health, and cytokines and to investigate the impact of age on these associations. In 174 female consecutive primary health care patients divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 40 publications
12
76
2
Order By: Relevance
“…Several previous studies have reported a positive relationship between poor SRH and increased cytokines such as IL-6 [17,35], IL-1β [15], IL-1ra [15], or TNF-α [15,16]. However, these findings are not always consistent when the studies are compared to each other.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several previous studies have reported a positive relationship between poor SRH and increased cytokines such as IL-6 [17,35], IL-1β [15], IL-1ra [15], or TNF-α [15,16]. However, these findings are not always consistent when the studies are compared to each other.…”
Section: Discussionmentioning
confidence: 58%
“…For instance, Janszky et al [17] found a positive relationship between poor SRH and IL-6, but not with IL-1ra, while Lekander et al [15] observed a positive relationship between poor SRH and IL1ra and TNF-α, but not with IL-6. A recent study by Unden et al [16] observed that the relationship between poor SRH and cytokines (TNF-α and IL-1β) was significant in elderly women (aged over 65 years), but not in younger women (aged <50 years). They also reported that the relationship between SRH and IL-6 or IL-1ra was not significant in any age group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The only reports of differential cytokine concentration by patient age involve serum levels of other cytokines as markers of inflammation and possible risk factors for morbidity and mortality (24)(25)(26). The addition of leukocytes to in vitro perfused rat ovaries has been found to increase the rate of ovulation (27) and exogenous IL-8 has been shown to effect follicular maturation in rabbits (28) and rats (29) similar to the administration of LH or hCG.…”
Section: Figurementioning
confidence: 96%
“…For example, a recent study in male veterans of behavioral activation, a psychological therapy that involves physical exposure to reminders of a trauma while being provided positive reinforcement, reduced PTSD symptoms as well as increased health-related quality of life (Jakupcak et al, 2010). Higher health-related quality of life has been linked to reductions in inflammation in other studies (Baturone et al, 2009;Booker, Olson, Pilarski, Noon, & Bahlis, 2009;Mommersteeg, Kupper, Schoormans, Emons, & Pedersen, 2010;Unden et al, 2007). Smoking cessation, which has been linked to reductions in peripheral inflammation (Goncalves et al, 2011), reduced PTSD symptoms and increased perceived health quality in male veterans .…”
Section: Epigenetic Modificationsmentioning
confidence: 95%